ANALISIS PENGUASAAN KOSAKATA BAHASA JEPANG SISWA KELAS 11 YANG MENGAMBIL PEMINATAN BAHASA JEPANG SMA N 1 TILATANG KAMANG - Mariska, Refi; Basri, Merri Silvia; Yohani, Adisthi Martha (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: The background of this research is because there are difficulties inlearning Japanese. This study aims to analyze the difficulties in mastering Japanesevocabulary of 11th grade students who take Japanese language interests at SMA N 1Tilatang Kamang. This study uses a quantitative method with a vocabulary testinstrument. The results of the study showed that the average test results of students were below the KKM, where 70.42% of students had incomplete scores with 13 students in the sufficient range and 7 students in the less than perfect range. And 8 students whohad scores above the KKM with good scores. Factors that influence student learningoutcomes are reviewed in terms of the use of media and methods to raise students'interest and enthusiasm for learning. Therefore, the researcher suggests furtherresearch to overcome this problem.Key Words: Learning Outcomes, Japanese Vacubulary, Japanese Language